Measurement of directed flow in Au+Au collisions at √𝑠𝑁⁢𝑁 = 19.6 and 27 GeV with the STAR event plane detector - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review, 2025)
In heavy-ion collision experiments, the global collectivity of final-state particles can be quantified by anisotropic flow coefficients (𝑣𝑛). The first-order flow coefficient, also referred to as the directed flow (𝑣1), describes the collective sideward motion of produced particles and nuclear fragments in heavy-ion collisions. It carries information on the very early stage of the collision, especially at large pseudorapidity (𝜂), where it is believed to be generated during the nuclear passage time. Directed flow therefore probes the onset of bulk collective dynamics during thermalization, providing valuable experimental guidance to models of the pre-equilibrium stage. In 2018, the Event Plane Detector (EPD) was installed in STAR and used for the Beam Energy Scan phase-II (BES-II) data taking. The combination of EPD (2.1<|𝜂|<5.1) and high-statistics BES-II data enables us to extend the 𝑣1 measurement to the forward and backward 𝜂 regions. In this paper, we present the measurement of 𝑣1 over a wide 𝜂 range in Au+Au collisions at √𝑠𝑁⁢𝑁= 19.6 and 27 GeV using the STAR EPD. The results of the analysis at √𝑠𝑁⁢𝑁= 19.6 GeV exhibit excellent consistency with the previous PHOBOS measurement, while elevating the precision of the overall measurement. The increased precision of the measurement also revealed finer structures in heavy-ion collisions, including a potential observation of the first-order event-plane decorrelation. Multiple physics models were compared to the experimental results. Only a transport model and a three-fluid hybrid model can reproduce a sizable 𝑣1 at large 𝜂 as was observed experimentally. The model comparison also indicates 𝑣1 at large 𝜂 might be sensitive to the QGP phase transition.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und viele weitere]
Gesehen am 22.09.2025